2001
DOI: 10.1074/jbc.m104038200
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of the Circumsporozoite Protein to Cell Surface Heparan Sulfate Proteoglycans Is Required for PlasmodiumSporozoite Attachment to Target Cells

Abstract: The major surface protein of malaria sporozoites, the circumsporozoite protein, binds to heparan sulfate proteoglycans on the surface of hepatocytes. It has been proposed that this binding event is responsible for the rapid and specific localization of sporozoites to the liver after their injection into the skin by an infected anopheline mosquito. Previous in vitro studies performed under static conditions have failed to demonstrate a significant role for heparan sulfate proteoglycans during sporozoite invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 37 publications
7
123
0
Order By: Relevance
“…This is supported by an earlier study in which soluble heparin required both these side groups for efficient inhibition of recombinant CSP binding to HepG2 cells (29). Furthermore, the spacing of charged groups on HS was important for binding to region I-plus because CS and DS were poor competitors even though they both have higher sulfate contents than HS.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is supported by an earlier study in which soluble heparin required both these side groups for efficient inhibition of recombinant CSP binding to HepG2 cells (29). Furthermore, the spacing of charged groups on HS was important for binding to region I-plus because CS and DS were poor competitors even though they both have higher sulfate contents than HS.…”
Section: Discussionsupporting
confidence: 68%
“…It is also clear that at least one of the cell surface ligands for CSP is HS (6,29,30), and there have been a number of studies suggesting that region II-plus (region II plus eight downstream residues) serves as the actual HS binding site (21,22,31). However, in these studies, the HS binding activity of region II-plus was determined indirectly in cell culture after HS-lyase digestion by showing diminished binding in Chinese hamster ovary cells deficient in proteoglycan synthesis and by heparin and HS prevention of proteolytic digestion of CSP.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of sulfate moieties to HSPG GAGs is one of these modifications and as stated above, liver HSPGs are more highly sulfated compared to HSPGs from other organs [43], suggesting that the degree of GAG chain sulfation could account for the selective targeting of sporozoites to the liver. Indeed it has been found that CSP binds preferentially to cells expressing HSPGs with highly sulfated GAGs [38,39] and that sporozoite attachment to cells decreases as the degree of GAG chain sulfation decreases [38]. One confounding issue is that these highly sulfated HSPGs are found behind the endothelial cell barrier.…”
Section: To the Livermentioning
confidence: 99%
“…Several lines of evidence suggest that this arrest is mediated by the interaction between the major surface protein of sporozoites, the circumsporozoite protein (CSP) and the highly sulfated HSPGs of hepatocytes [35][36][37][38][39]. Recombinant CSP binds specifically to hepatic HSPGs and in vivo, the physiologic ligands for hepatic HSPGs, namely lactoferrin and lipoprotein remnants, delay CSP clearance from the circulation and inhibit sporozoite infection of hepatocytes [40].…”
Section: To the Livermentioning
confidence: 99%
“…1B) whereas capping is observed for apical invasion proteins. Shaving occurs continuously as the parasite penetrates and is (Dubremetz et al ., 1985;Grimwood and Smith, 1995) Yes (Mineo and Kasper, 1994;He et al ., 2002) Unknown TgMIC1/MIC4/MIC6 (Meissner et al ., 2002b) Yes (Fourmaux et al ., 1996;Brecht et al ., 2001) MPP1 TgMIC2/M2AP Yes (Carruthers et al ., 1999;Harper et al ., 2004) MPP1 Zhou et al ., 2004) TgMIC3/MIC8 (Meissner et al ., 2002b) Yes (Garcia-Reguet et al ., 2000;Meissner et al ., 2002b) MPP1 TgAMA1 (Donahue et al ., 2000;Hehl et al ., 2000) Unknown MPP1 (S. A. Howell, M. J. Blackman and V. B. Carruthers, unpublished) Plasmodium PfTRAP and PbTRAP (Bhanot et al, 2003;Silvie et al ., 2004) Yes (McCormick et al ., 1999;Akhouri et al ., 2004) Serine protease (Silvie et al .. 2004) PfCSP (Stewart and Vanderberg, 1988; Yes (Pinzon-Ortiz et al ., 2001) Unknown PfMSP1/MSP6/MSP7 (Stafford et al ., 1994) Yes (Goel et al ., 2003;Li et al ., 2004) MESH (Howell et al ., 2003) PkAMA1 and PfAMA1 (Deans et al ., 1984;Howell et al ., 2001) Yes (Fraser et al ., 2001) MESH (Howell et al ., 2003) EBL-DBP (Camus and Hadley, 1985;Haynes et al ., 1988) Yes (Camus and Hadley, 1985;Haynes et al ., 1988) Unknown Py235 (Ogun and Holder, 1996) Yes (Ogun and Holde...…”
Section: Primed For Penetrationmentioning
confidence: 99%